Modelling of traffic capacity under traffic accident. (1st April 2020) - Ling, Yu; Pan, Zhang; Zhang, Yitong; Jia, Siyu; Sun, Baoyun; Huang, Mingxia
In this paper, the traffic characteristics of urban roads under traffic accidents are analysed from three aspects: the traffic volume characteristics, the definition of accident sections and the evolution characteristics of traffic capacity. On this basis, the theoretical analysis on road traffic capacity under traffic accidents is carried out and the capacity model is established. Guided by traffic volume theory and lane-changing rules, the correction coefficients of various influencing factors are simulated by adjusting the parameters on VISSIM, and the results are used to analyse the influencing factors of traffic capacity under traffic conditions. The curve fitting of the obtained data were conducted by MATLAB, a regression model of the reduction factor of traffic capacity of urban roads under traffic accident and each influencing factor and the actual traffic capacity model are built. Taking the traffic accident on the urban roads as an example, the quantitative analysis is made on the traffic capacity of urban road under the traffic accident to verify the proposed model and the results show its effectiveness.